Peran Terapi Bekam dalam Meningkatkan Kebahagiaan Perspektif Al-Ghazali - Siti Nurjanah, Dian; Rismanto, Firman; Nursaadah, Olvia (Jurnal Riset Agama, 2025)
In Islam, cupping is not only a physical therapy, but also has a spiritual dimension. In addition to restoring health, cupping therapy is also used as a means of maintaining health. Imam Al-Ghazali viewed happiness as a state of harmony between the body, soul, and spirit. This study aims to analyze the role of cupping therapy in stimulating happiness when viewed from Al-Ghazali's perspective. This study uses an exploratory descriptive design. The data collection techniques used are questionnaires and interviews. The instrument used is a happiness instrument that refers to Imam Al-Ghazali's theory of happiness in Kimiya Al-Sa'adah. The population and sample used are cupping therapy clients from Rumah Sehat Zahira. A total of 49 respondents filled out the questionnaire, while 3 respondents were interviewed. The analysis technique in the exploratory descriptive design was carried out in two stages, namely quantitative data analysis followed by qualitative data analysis. The quantitative data analysis technique used descriptive statistics, while the qualitative data analysis used the Miles & Huberman technique. The results of this study found that 63.3% of cupping therapy clients at RSH Zahira were in the high happiness category. The happiness felt after cupping therapy is caused by two things: first, the complaints that were previously experienced have improved; second, cupping therapy is a sunnah of the Prophet Muhammad Saw., so performing it is an act of obedience. These two things create a feeling of relief and happiness. It can be concluded that the majority of cupping clients report high levels of happiness due to the creation of a balance between physical and spiritual needs.